Musizierende Wandervögel (Geige und Querflöte) in der Nähe eines Steinmauers - Hund (1918)
soziale Fragen;Leben in der Gesellschaft (allgemein);Leben in der Gesellschaft (speziell);Haustier;Hund Wirtschaft;Industrie;verschiedene Industriezweige;Musikinstrument soziale Fragen;Kultur und Religion;Kunst;Musik politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Jugendbewegung soziale Fragen;Leben in der Gesellschaft (allgemein);Freizeit